2019
DOI: 10.1029/2019jc015193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrological Conditions on the Biogeochemical Dynamics of Suspended Particulate Organic Matter in the Upper Mixed Layer of the Southern East China Sea

Abstract: We investigate suspended particles collected from the upper mixed layer in the inner shelf of the southern East China Sea during autumn 2013 for carbon and nitrogen (POC and PN) contents and their isotope compositions (δ13C and δ15N) along with hydrographic parameters to understand the sources and dynamics of particulate organic matter (POM) in the study area. Results indicated that the extensive hydrological processes affect the biogeochemical composition of suspended POM, as revealed by the horizontally mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 123 publications
(199 reference statements)
0
5
0
Order By: Relevance
“…In this study, the lowest and highest POC concentrations were 1.8 and 77.1 μg C L −1 , respectively, with mean depth-normalized integrated values ranging from 12.7 (±2.3) to 21.6 (±5.2) μg C L −1 ( Figure 4 c). The concentration was in the range of the reported value, 2–99 μg C L −1 , in the KW [ 35 , 36 , 37 , 38 ]. Notably, the POC value is relatively low in the KW compared to that in the East China Sea (ECS) shelf ecosystem; for example, its mean value over the entire ECS shelf was 227.5 (±141.9) μg C L −1 [ 39 ].…”
Section: Resultsmentioning
confidence: 82%
“…In this study, the lowest and highest POC concentrations were 1.8 and 77.1 μg C L −1 , respectively, with mean depth-normalized integrated values ranging from 12.7 (±2.3) to 21.6 (±5.2) μg C L −1 ( Figure 4 c). The concentration was in the range of the reported value, 2–99 μg C L −1 , in the KW [ 35 , 36 , 37 , 38 ]. Notably, the POC value is relatively low in the KW compared to that in the East China Sea (ECS) shelf ecosystem; for example, its mean value over the entire ECS shelf was 227.5 (±141.9) μg C L −1 [ 39 ].…”
Section: Resultsmentioning
confidence: 82%
“…The atmospheric deposition has significant influence on the phytoplankton bloom dynamics. There are low ratios of C:N (around 2.4-6.5) in the study region (Liu et al, 2019). They found that Kuroshio-induced biological N fixation plays an important role in supporting the marine production in the region.…”
Section: Characteristics Of Ecmsmentioning
confidence: 83%
“…Anthropogenic nutrient enrichment in these waters has led to severe eutrophication (Kim et al, 2011), which is exacerbated by atmospheric nutrient (N) deposition threatening the structure and function of regional terrestrial and aquatic ecosystems (Liu et al, 2013). The extremely high N loading has caused Chinese coastal waters to transition from N to P (phosphorus) limited status (Kim et al, 2011;Mackey et al, 2017; T. H. Huang et al, 2019;Liu et al, 2019). The atmospheric deposition has significant influence on the phytoplankton bloom dynamics.…”
Section: Characteristics Of Ecmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, this topic has attracted extensive attention, yet the role of marginal seas as a carbon source or sink remains under debate (Borges et al, 2005;Cai, 2011;Dai et al, 2013Dai et al, , 2022. Marginal seas are characterized by complex hydrodynamic processes that are tightly linked to organic matter cycling (Bao et al, 2018;Chen et al, 2021;Guo et al, 2018;Liu et al, 2019;Pedrosa-Pamies et al, 2013). In particular, on ocean margins influenced by large rivers, the convergence of plumes with ocean currents generates a series of fronts and exerts a pronounced impact on phytoplankton production and the development of hypoxia in bottom waters (Guo et al, 2020;Lv et al, 2022;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%